BROODSTOCK CONDITIONING FOR THE TROPICAL ABALONE (Hatiotis asinina) UNDER DIFFERENT COMBINATION OF PHOTOPERIOD AND WATER TEMPERATURE - D. E. Djoko Setyono (Research Center for Fisheries, 2005)
The main purpose ot this study is to understand the influcnce of external parameters, i.e, photoperiod and water temperature, on gonadal maturation of tropical abalone (Haliotis asinina) in southorn Lombok waters, NTB